Grand Challenges in Bio-Nanotechnology to Manage the COVID-19 Pandemic - Paliwal, Praveena; Sargolzaei, Saman; Bhardwaj, Sheetal K.; Bhardwaj, Vinay; Dixit, Chandra; Kaushik, Ajeet (Frontiers in Nanotechnology, 2020)
Recent COVID-19 pandemic outbreak, a human beta coronavirus severe acute respiratory syndrome (SARS-CoV-2) virus infection, has severely affected the world and is not yet in full control due to lacking rapid diagnostics and therapeutics. This viral infection is steadily increasing life loss and emerged as a significant socio-economic burden for every class of the world. As a result, it has brought many countries united for exploring molecular biology, biomedical science, and nanotechnology aspects to manage COVID-19 successfully. As of now, the current priority is to investigate novel therapies of high efficacy and smart diagnostics tools for early-stage disease diagnostics along with monitoring. Keeping these advancements and challenges into consideration, this perspective article mainly highlights the contribution and possibilities of bio-nanotechnology to manage the COVID-19 pandemic, even in a personalized manner. Authors also pinpoint barriers in the utilization of current bio-nanotechnology to facilitate a more accurate understanding of COVID-19 and to lead in the way of personalized health and wellness. Further, we follow discussion towards aspects and challenges in upcoming bio-nanotechnology approaches for COVID-19 management. In this progressive option report, bio-nanotechnologies enriched with the power of artificial intelligence and optimized at the personalized level will lead to a sustainable treatment and cure strategy at the global population scale.